2010
DOI: 10.1007/s10570-010-9451-5
|View full text |Cite
|
Sign up to set email alerts
|

UV light-induced grafting of fluorinated monomer onto cellulose sheets

Abstract: The surface modification of cellulose opens the way towards almost infinite new applications, making it suitable for functional and sustainable materials. Additionally, it also represents a possibility for up-grading traditional products. In this work, we report about the photo-induced grafting onto cellulose substrates of a highly fluorinated acrylic monomer, characterized by a long perfluoropolyether chain. Grafting changed the surface composition, as assessed by XPS measurements: the values of F/C atomic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…This repellency can be achieved by implementing a thin surface layer of water repellent chemicals on textile fibres by the modification of surface energy of textiles with minimal effects on other functional properties like strength, flexibility, breathability, softness etc. (Bongiovanni R 2011 andFerrero E 2012). Polymeric coating on cotton fabric must secure good homogeneity with preferred properties without deteriorating fabric's comfort ability like handle, breathability etc.…”
Section: Introductionmentioning
confidence: 99%
“…This repellency can be achieved by implementing a thin surface layer of water repellent chemicals on textile fibres by the modification of surface energy of textiles with minimal effects on other functional properties like strength, flexibility, breathability, softness etc. (Bongiovanni R 2011 andFerrero E 2012). Polymeric coating on cotton fabric must secure good homogeneity with preferred properties without deteriorating fabric's comfort ability like handle, breathability etc.…”
Section: Introductionmentioning
confidence: 99%
“…Various initiation techniques, including chemical [5], photochemical [11], and high energy radiation [6] methods, have been used to activate or initiate the backbone cellulose polymer. Radiationinduced graft copolymerization in hydrogel preparation is one of the most promising methods because of its ease of handling at room temperature, deep penetration in polymer matrix, rapid and uniform formation of active sites for initiating grafting, and lack of need for chemical initiator.…”
Section: Introduction *mentioning
confidence: 99%
“…16 -20 The copolymerization of acrylic and methacrylic PFPE products with hydrogenated monomers can be used to tune the properties of PFPE fluoropolymers. 10,11,13,21,22 Depending on the coexistence of fluorinated matrix and hydrogenated phase, there is usually an improvement of the mechanical performances and the obtaining of particular properties such as amphiphilicity and anti-fouling properties. It was recently reported that co-networks based on the intermixing of hydrophilic moieties and hydrophobic PFPE structures have potential applications in fields like biomaterials and nanotechnology.…”
Section: Introductionmentioning
confidence: 99%